معضلة الاستقلال في الوطن العربي - غـــــزال, أحمـــد (revue mofakir, 2018)
لقد نجحت الدولة العربية أن تصمد لمدة طويلة منذ استقلالها، رغم أن كل القراءات كانت تتنبأ بانهيارها بعد ولادتها المشوهة بوقت قليل، لكن الذي حدث هو أنه بعد هذه الولادة القيصرية للدولة القطرية، نجحت في إرساء مؤسساتها، ونجحت بعض الشيء في تقديم بعض الخدمات كالصحة والتعليم والتنمية، وتكريس هويتها الخاصة بها، وإرغام المواطنين للاذعان لها، فأصبحوا يقبلو ن بها ويتحمسون إليها، ولا يمكن البتة إجحاف ومحو مثل هذه الانجازات أو التقليل من شأنها . لكن الحقيقة التي لا يمكن التغطية عنها أن هذه الدولة القطرية العربية تعيش أزمة، وأصبح واضحا أن الدولة الحديثة التي غرست بناها في معظم الدول العربية أثناء خضوعها للاستعمار الأوروبي ، قد نقلت هذه الأقطار مؤسسات اقتصادية وإدارية وسياسية من جنس تلك التي كانت قائمة في الدول المستعمرة، وورثت أزمات ومشكلات وويلات تحمل بصمات مرحلة الاحتلال الأوروبي، أين غرس المحتل نفسه النواة الأولى لنشأة ما يسمى بالدولة القطرية العربية .   Abstract: Arab state has managed to hold up for a long time since its independence, although all readings were predicting its collapse shortly after its deformed born, but what happened is that after the country state caesarean section deliverance, it succeeded in establishing its institutions, and somewhat in the providing some services, such as health and education, and development. Furthermore, it has exhibited a great potentiality in dedicating its own identity, and forcing citizens not only to comply with it but to accept it and to become enthusiastic about it. For these reasons, it is not judicious at all to prejudice and erase or underestimated such achievements. But the reality that cannot be covered is that Arab state suffers from a serious crisis. Indeed, it becomes clear that the modern state, which implanted in most Arab countries while undergoing European colonialism, has brought to these countries economic, administrative and political institutions of the kind of those that existed in the colonial countries. Consequently, the modern state has inherited some crises, problems and ravages that hallmark the European occupation phase, where the occupier has auto-planted as the first nucleus for the emergence of the so-called country Arab state.